2012
DOI: 10.1111/j.1744-7429.2012.00900.x
|View full text |Cite
|
Sign up to set email alerts
|

Invertébrés Sans Frontières: Large Scales of Connectivity of Selected Freshwater Species among Caribbean Islands

Abstract: The freshwater fauna (crustaceans, molluscs, fish) of many tropical islands in the Caribbean and Pacific share an amphidromous lifecycle, meaning their larvae need to develop in saline conditions before returning to freshwater as juveniles. This community dominates the freshwaters of much of the tropics, but is poorly known and at risk from development, in particular dam construction. Amphidromy can theoretically lead to dispersal between different freshwater areas, even to distant oceanic islands, via the sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 64 publications
(134 reference statements)
3
20
0
2
Order By: Relevance
“…This result correlates with the general notion that genetic differentiation of populations of amphidromous shrimp is rare or at most weakly expressed over larger scales (> 1000 km) [75]. A similar result was encountered in the distantly related palaemonid species, Cryphiops caementarius (see [76]), as well as in amphidromous representatives of the Atyidae [17], the other main family of freshwater shrimps. Interestingly, the hierarchical AMOVA suggests that genetic differentiation does fall within a widely discussed biogeographic barrier between the southern populations and the south-east transition zone in the proximity of Algoa Bay [27].…”
Section: Discussionsupporting
confidence: 84%
“…This result correlates with the general notion that genetic differentiation of populations of amphidromous shrimp is rare or at most weakly expressed over larger scales (> 1000 km) [75]. A similar result was encountered in the distantly related palaemonid species, Cryphiops caementarius (see [76]), as well as in amphidromous representatives of the Atyidae [17], the other main family of freshwater shrimps. Interestingly, the hierarchical AMOVA suggests that genetic differentiation does fall within a widely discussed biogeographic barrier between the southern populations and the south-east transition zone in the proximity of Algoa Bay [27].…”
Section: Discussionsupporting
confidence: 84%
“…Although sampling bias cannot be ruled out, connectivity patterns in M. lar may thus be explained by factors other than geographic distance only. Ocean currents may have a strong influence on population genetic structuring (White et al 2010;Page et al 2013). However, on a large geographical scale, present-day oceanic currents are usually not fully consistent with patterns of connectivity in marine species (Benzie 1998;Lessios 1998;Planes and Fauvelot 2002).…”
Section: Isolation Of Peripheral Geographic Locationsmentioning
confidence: 97%
“…Crandall et al 2010 and references therein). Accordingly, several population genetic studies have shown that amphidromous organisms with long-lived larvae display low or non-existent genetic structure among populations (Chubb et al 1998;Hodges and Allendorf 1998;Myers et al 2000;Waters et al 2000;Kano and Kase 2004;Berrebi et al 2005;Page et al 2013). However, most of these studies have been undertaken at relatively small geographical scale (i.e., island or archipelago).…”
Section: Introductionmentioning
confidence: 97%
“…Cook et al, 2011;Schmidt et al, 2011a;Page et al, 2012;Hughes, Huey & Schmidt, 2013;Hughes et al, 2014). Molecular markers are often used to explore the life history of diadromous species (e.g.…”
Section: Introductionmentioning
confidence: 99%